Comparing the Effect of Nanomaterial and Traditional Fillers on the Asphalt Mixture Properties - Hamedi, Gholam Hossein; Sohrabi, Mohsen; Sakanlou, Farhad (Salehan Institute of Higher Education, 2019)
Several parameters affect asphalt mix performance against loading and environmental conditions. Minor changes in the filler amount or type can cause obvious changes in the asphalt mixture properties. Accordingly, in this research attempts have been made to optimally make asphalt mixture strong against loading and environmental conditions by changing the type, size and percentage of filler used in asphalt mixture. In this line, the effect of two types of cement and nano-silica fillers in two different percentages was investigated and compared as an alternative for part of the main filler in asphalt mixture samples made by two types of limestone and granite aggregate. Cement filler by 2% and 4% of the aggregate mass as the alternative for part of the main filler is added to stone materials before mixing with binder, but nano-silica filler by 2% and4 % of weight of the binder as the alternative for part of the main filler is added to binder and a modified and homogeneous binder is produced using a high speed mixer. In the following, considering the optimum binder content for each mixture, resilient modulus tests were conducted to determine the strength performance against loading and indirect tensile strength ratio was used to determine moisture sensitivity of asphalt mixtures. Results obtained from resilient modulus tests show that the use of nano-silica and cement has been capable of favorably improving the resilient modulus of samples containing these two types of fillers. The improvement of the resilient modulus of samples containing nano-silica is very significant. Additionally, the studies conducted based on the indirect tensile strength ratio show that both types of alternative fillers, especially cement has been capable of desirably improve the strength of asphalt mixtures against moisture damage.